Al-doped transition metal nitride composite coating as well as preparation method and application thereof
By depositing an Al-doped transition metal nitride composite coating on the surface of the proton exchange membrane water-electrolytic bipolar plate, the problem of corrosion of the bipolar plate in high oxygen potential and acidic environment is solved, and high conductivity and high corrosion resistance are achieved, reducing costs and extending service life.
Patent Information
- Application Number
- CN202510329334.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-20
AI Technical Summary
The proton exchange membrane water electrolytic bipolar plate is prone to corrosion in high oxygen potential and acidic environments, resulting in reduced performance and shortened service life. The existing technology requires the use of precious metals for modification, which is relatively expensive.
Al-doped transition metal nitride composite coating is used to deposit titanium nitride coating and titanium nitride aluminum coating on the surface of the bipolar plate in sequence to form a double-layer structure to improve conductivity and corrosion resistance, and avoid the use of precious metals.
The high conductivity and corrosion resistance of bipolar plates are achieved, which reduces manufacturing costs and significantly extends the service life of bipolar plates.
Smart Images

Figure CN119843218A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of surface engineering protection, and more specifically to an Al-doped transition metal nitride composite coating and a preparation method and application thereof. Background Art
[0002] Hydrogen energy has the advantages of high energy density, water as combustion product, and no harmful emissions. At present, in the hydrogen production industry, water electrolysis accounts for about 3% of the annual hydrogen production scale. It is the most environmentally friendly and efficient preparation method, with abundant raw materials and environmentally friendly.
[0003] The advantages of proton exchange membrane water electrolyzers, such as high efficiency, small size, flexible operation, rapid response, compact system design and extended dynamic operating range, are becoming increasingly apparent, and have become the focus of current research and development in the field of green hydrogen production.
[0004] As a key component of the proton exchange membrane water electrolyzer, the bipolar plate not only provides mechanical support and current distribution for the membrane electrode assembly, but also provides the necessary gas-liquid channels to ensure the normal transmission and uniform distribution of water and gas. It also occupies most of the volume and cost, accounting for about 70% of the overall mass and 30% of the price.
[0005] Due to the high oxygen potential at the anode of the electrolyzer, the oxidative active oxygen generated during water electrolysis, and chemical and electrochemical corrosion in an acidic environment, the proton exchange membrane water electrolysis bipolar plate must have high mechanical strength, high corrosion resistance, low interfacial contact resistance, light weight, and effective manufacturability. Currently, graphite, metal, and polymer blends with carbon are three candidate materials for bipolar plates. Compact graphite can meet most of the requirements of bipolar plates. However, it has challenges such as toughness, corrosion at high potentials of >1.5V in water electrolysis mode, and poor manufacturability. Polymers blended with carbon have advantages in effective manufacturability, but still suffer from poor electronic conductivity. Therefore, metals are good alternative candidates for bipolar plates because they have excellent manufacturability, are impermeable to gas and water, have high thermal and electrical conductivity, and are cost-effective.
[0006] In the working environment of a proton exchange membrane water electrolyzer, semi-conductive oxides are formed on the surface of the metal bipolar plate due to anodic oxidation, which has a negative impact on the performance and durability of the electrolyzer. Once corrosion occurs, metal ions are released that may poison the catalyst and the proton exchange membrane, reducing the output power and service life of the fuel cell. At the same time, the surface of the metal bipolar plate reacts with oxygen to form a passivating oxide layer. This layer increases the contact resistance between the bipolar plate and the electrode, and the battery performance is significantly reduced. Therefore, it is necessary to use conductive and corrosion-resistant materials to modify the surface of the metal bipolar plate, and surface coating is the most commonly used modification method; among them, in order to have both high conductivity and high corrosion resistance, the researchers introduced precious metals into the surface coating, and the loading range of the precious metals is still 1 mg cm -2 ~3mg cm -2 , the cost is relatively high. Summary of the invention
[0007] In view of the above problems, the present invention provides an Al-doped transition metal nitride composite coating and a preparation method and application thereof. The Al-doped transition metal nitride composite coating of the present invention does not require the use of precious metals, thereby reducing costs, and at the same time has excellent electrical conductivity and corrosion resistance.
[0008] The first object of the present invention is to provide an Al-doped transition metal nitride composite coating, wherein the Al-doped transition metal nitride composite coating is a titanium nitride coating and a titanium aluminum nitride coating deposited sequentially from bottom to top on a substrate; the thickness of the Al-doped transition metal nitride composite coating is 240nm~270nm.
[0009] In the Al-doped transition metal nitride composite coating structure of the present invention, the titanium nitride coating is a coating relatively close to the bipolar plate, and the titanium aluminum nitride coating is a coating relatively far from the bipolar plate. Specifically and exemplarily, the transition metal compound composite coating is deposited on the surface of the bipolar plate, and the material of the bipolar plate is titanium alloy or stainless steel; explanatory, when the material is titanium alloy, the titanium nitride coating in the transition metal compound composite coating is the first coating deposited on the surface of the metal substrate, and the titanium aluminum nitride coating is deposited after the titanium nitride coating; the titanium nitride coating is considered to be an enhanced layer in the double-layer coating because titanium nitride may provide self-healing properties for the entire coating. Therefore, oxidation of the metal substrate inside the coating can solve defects in other coatings.
[0010] During the deposition process, the double-layer coating structure can intercept the growth of columnar crystals, improve the dislocation of defects such as pores in the single-layer coating, and improve the density of the coating. By changing the modulation ratio of the titanium nitride coating and the titanium aluminum nitride coating, the pore defect matching between the coatings is adjusted to improve the conductivity and corrosion resistance of the bipolar plate.
[0011] In a preferred embodiment of the present invention, the preferred crystal plane orientation of the titanium nitride coating is (200), and the thickness of the titanium nitride coating is 90 nm to 180 nm.
[0012] In a preferred embodiment of the present invention, the preferred crystal plane orientation of the titanium aluminum nitride coating is (200), and the thickness of the titanium aluminum nitride coating is 90 nm to 180 nm.
[0013] A second object of the present invention is to provide a method for preparing the Al-doped transition metal nitride composite coating, comprising the following steps: Under a protective gas atmosphere, a titanium nitride target is used as a target material, and a first pulse laser deposition is performed on the surface of a substrate to form a titanium nitride coating.
[0014] Under a protective gas atmosphere, a titanium aluminum nitride target is used as a target material, and a second pulse laser deposition is performed on the surface of the titanium nitride coating to form a titanium aluminum nitride coating, thereby obtaining an Al-doped transition metal nitride composite coating.
[0015] In a preferred embodiment of the present invention, in the first pulse laser deposition, the gas pressure of the reaction chamber is 2Pa~4Pa, the deposition temperature is 400°C, and the deposition time is 800s~1000s.
[0016] In a preferred embodiment of the present invention, in the second pulse laser deposition, the gas pressure of the reaction chamber is 2Pa~4Pa, the deposition temperature is 400°C, and the deposition time is 1000s~1200s.
[0017] In a preferred embodiment of the present invention, the titanium aluminum nitride target is composed of the following components in percentage by mass: 6% aluminum and 94% titanium nitride.
[0018] In a preferred embodiment of the present invention, the purity of the titanium nitride target is 99.9%, and the purity of the titanium aluminum nitride target is 99.9%.
[0019] The third object of the present invention is to provide the use of the above-mentioned Al-doped transition metal nitride composite coating in a proton exchange membrane fuel cell or a proton exchange membrane water electrolyzer.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The Al-doped transition metal nitride composite coating provided by the present invention is composed of a titanium nitride coating and a titanium aluminum nitride coating deposited in sequence to form a composite double-layer structure, thereby improving the compactness of the coating; the titanium nitride and the titanium aluminum nitride form a double-layer structure, and when deposited on a substrate, the probability of the corrosive medium in the electrolyte penetrating the coating through pore defects and the like as channels, thereby corroding the substrate and ultimately causing coating failure can be effectively reduced; the Al-doped transition metal nitride composite coating of the present invention is deposited on a substrate that has both excellent electrical conductivity and corrosion resistance, avoids the use of precious metals, reduces manufacturing costs, and significantly prolongs the service life of the substrate.
[0021] The lattice parameters of titanium nitride and aluminum nitride are 0.424nm and 0.412nm, respectively. Al atoms replace Ti atoms, resulting in changes in internal stress and lattice deformation of the titanium aluminum nitride coating, resulting in an overall rightward shift of the X-ray diffraction peak of the titanium aluminum nitride coating. After the third element Al is incorporated into the titanium nitride hard coating, the corrosion resistance of titanium aluminum nitride can be improved due to the formation of Al2O3, excellent temperature, oxidation resistance and mechanical properties. The titanium nitride coating with relatively low hardness and high corrosion resistance is considered to be an adhesive coating between the metal substrate and the outermost layer. The titanium nitride coating is an enhanced layer in the coating because titanium nitride may provide self-healing properties for the entire coating. Therefore, oxidation of the metal substrate inside the coating can solve defects in other coatings. Due to the hardness of titanium aluminum nitride, good conductivity and superior corrosion resistance of the coating, it can be used as an outer layer.
[0022] The present invention prepares an Al-doped transition metal nitride composite coating with both high conductivity and high corrosion resistance through a pulsed laser deposition process. The coating ensures the uniformity of the phase and improves the compactness of the coating by adopting a pulsed laser deposition process. In the laser pulse deposition, the present invention changes the coating process, nitrogen pressure, substrate temperature, deposition time and other parameters to obtain a single-layer coating with uniform component phases, avoids the generation of multiple phases in the single layer, reduces the influence of impurity phases, and ensures the corrosion resistance of the coating; in addition, a double-layer structure of an Al-doped transition metal compound composite coating is prepared by sequentially depositing a titanium nitride coating and a titanium aluminum nitride coating. Through the double-layer design, defects such as pores in each layer are effectively dislocated, thereby improving the compactness of the coating and effectively reducing the probability that the corrosive medium in the electrolyte penetrates the coating through defects such as pores as channels to corrode the substrate, thereby causing the coating to fail. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the Al-doped transition metal nitride composite coating of the present invention.
[0024] Figure 2 This is a surface scan of the Al-doped transition metal nitride composite coating prepared in Example 1 of the present invention.
[0025] Figure 3 This is a cross-sectional scan of the Al-doped transition metal nitride composite coating prepared in Example 1 of the present invention.
[0026] Figure 4 It is a comparison chart of the dynamic potential scanning test results of Example 1~Example 2 of the present invention and Comparative Example 1-Comparative Example 2.
[0027] Figure 5 1 is a comparison chart of the interface contact resistance test results of Example 1 to Example 2 of the present invention and Comparative Example 2. Figure 5 A partial enlarged view of .
[0028] Reference numerals: 1 - substrate, 2 - titanium nitride coating, 3 - titanium aluminum nitride coating. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In addition, the terms "comprises," "comprising," and "having," and any variations thereof, are intended to cover non-exclusive inclusions. For example, a process, method, system, product, or apparatus that includes a series of steps or elements is not necessarily limited to those steps or elements explicitly listed, but may include other steps or elements not explicitly listed or inherent to such process, method, product, or apparatus.
[0031] On the market, the corrosion current density of metal bipolar plates obtained by modifying the surface of metal bipolar plates by loading precious metals on the coating is basically lower than 1×10 -7 A.cm -2 However, the presence of precious metals leads to high preparation costs. Based on this, the present invention provides an Al-doped transition metal nitride composite coating that combines high conductivity and high corrosion resistance. Figure 1 The Al-doped transition metal nitride composite coating provided by the present invention is a double-layer structure, including a titanium nitride coating and a titanium aluminum nitride coating deposited sequentially.
[0032] The Al-doped transition metal nitride composite coating provided by the present invention is used for deposition on the surface of a substrate, and is composed of a titanium nitride coating and a titanium aluminum nitride coating deposited in sequence to form a double-layer structure, thereby improving the compactness of the coating. In the coating provided by an embodiment of the present invention, titanium nitride and titanium aluminum nitride are selected to form a double-layer structure, which is deposited on a bipolar plate, and can effectively reduce the probability that the corrosive medium in the electrolyte penetrates the coating through pore defects and the like as channels, thereby corroding the substrate and ultimately causing coating failure. In this way, the bipolar plate can have both excellent electrical conductivity and corrosion resistance, which not only reduces the manufacturing cost of the bipolar plate, but also significantly extends the service life of the bipolar plate. The improvement measures of the present invention are of great significance for improving the performance, stability and economy of the overall equipment.
[0033] Example 1 This embodiment provides a method for preparing an Al-doped transition metal nitride composite coating having both high conductivity and high corrosion resistance, and the specific preparation steps are as follows: S1. TA1 commercial titanium plate was selected as the substrate. The substrate was polished with SiC paper with particle sizes of 240#, 600#, 1000#, 2000# and 3000# in sequence, and then the surface of the substrate was polished into a mirror state with diamond polishing paste with a particle size of 0.5µm; the polished substrate was ultrasonically cleaned with acetone, alcohol and deionized water, and the cleaning time was 15 minutes respectively, and finally the substrate was naturally air-dried.
[0034] S2. The air-dried substrate is fixed on the sample stage and transferred into the deposition chamber. The substrate is heated to 400°C and the vacuum degree of the chamber is less than 2×10 -4 After reaching 4 Pa, high-purity nitrogen was introduced and the nitrogen flow rate was adjusted to keep the nitrogen pressure at around 4 Pa. The deposition target was set to a titanium nitride target with a purity of 99.9%, the laser frequency was set to 8 Hz, the laser energy was set to 3342 mJ, the deposition time was set to 1000 s, and the laser switch was turned on to start depositing the titanium nitride coating.
[0035] S3. After the deposition of the titanium nitride coating is completed, the thickness of the titanium nitride coating is 127.67 nm. Turn off the laser switch and set the deposition target to a titanium aluminum nitride target with a purity of 99.9%, wherein the mass percentage of Al in the titanium aluminum nitride target is 6%, and the mass percentage of titanium nitride is 94%. The substrate temperature, nitrogen pressure, laser frequency and laser energy remain unchanged. The deposition time is 1000 s and the laser is turned on.
[0036] S4, turn off the laser switch, cool naturally to room temperature, take it out from the chamber, the thickness of the titanium aluminum nitride coating is 132.98nm, and finally the Al-doped transition metal nitride composite coating deposited on the surface of the TA1 commercial titanium plate is obtained, and the total thickness of the Al-doped transition metal nitride composite coating is 260.65nm.
[0037] Figure 2 This is the surface scanning test result of the Al-doped transition metal nitride composite coating of Example 1, and it can be seen that the surface of the prepared coating is complete and uniform; Figure 3 This is the cross-sectional scanning test result of the Al-doped transition metal nitride composite coating of Example 1. It can be seen that the prepared coating presents a columnar crystal structure.
[0038] The self-corrosion current density of the composite coating sample is about 1.0×10 -8 A.cm -2 , at a working voltage of 2.0 V, its corrosion current density is less than 1×10 -7 A.cm -2 , comparable to or even better than the precious metal coatings on the market; the interface contact resistance is about 8.55mΩ·cm 2 While maintaining high corrosion resistance, it also greatly improves the conductivity of the substrate, taking into account both high corrosion resistance and conductivity without the need to load precious metals.
[0039] Example 2 This embodiment provides a method for preparing an Al-doped transition metal nitride composite coating having both high conductivity and high corrosion resistance, and the specific preparation steps are as follows: S1. TA1 commercial titanium plate was selected as the substrate. The substrate was polished with SiC paper with particle sizes of 240#, 600#, 1000#, 2000# and 3000# in sequence, and then the surface of the substrate was polished into a mirror state with diamond polishing paste with a particle size of 0.5µm; the polished substrate was ultrasonically cleaned with acetone, alcohol and deionized water, and the cleaning time was 15 minutes respectively, and finally the substrate was naturally air-dried.
[0040] S2. The air-dried substrate is fixed on the sample stage and transferred into the deposition chamber. The substrate is heated to 400°C and the vacuum degree of the chamber is less than 2×10 -4 After reaching 4 Pa, high-purity nitrogen was introduced and the nitrogen flow rate was adjusted to keep the nitrogen pressure at around 4 Pa. The deposition target was set to a titanium nitride target with a purity of 99.9%, the laser frequency was set to 8 Hz, the laser energy was 3342 mJ, the deposition time was 800 s, and the laser switch was turned on to start depositing the titanium nitride coating.
[0041] S3. After the deposition of the titanium nitride coating is completed, the thickness of the titanium nitride coating is 121.64 nm. Turn off the laser switch and set the deposition target to a titanium aluminum nitride target with a purity of 99.9%, wherein the mass percentage of Al in the titanium aluminum nitride target is 6%, and the mass percentage of titanium nitride is 94%. The substrate temperature, nitrogen pressure, laser frequency and laser energy remain unchanged. The deposition time is 1200 s and the laser is turned on.
[0042] S4, turn off the laser switch, cool naturally to room temperature, take it out from the chamber, the thickness of the titanium aluminum nitride coating is 123.94nm, and finally the Al-doped transition metal nitride composite coating deposited on the surface of the TA1 commercial titanium plate is obtained, and the total thickness of the Al-doped transition metal nitride composite coating is 245.58nm.
[0043] The self-corrosion current density of the coating sample is about 1.18×10 -8 A.cm -2 , at a working voltage of 2.0 V, its corrosion current density is less than 5×10 -7 A.cm -2 , comparable to or even better than the precious metal coatings on the market; the interface contact resistance is about 13.28mΩ·cm 2 While maintaining high corrosion resistance, it also greatly improves the conductivity of the substrate, taking into account both high corrosion resistance and conductivity without the need to load precious metals.
[0044] Compared with Example 1, after changing the deposition time in this example, the modulation ratio of the titanium nitride coating and the titanium aluminum nitride coating changes, and the thickness of the two coatings changes, which affects the matching degree of the coating pore defects.
[0045] Example 3 This embodiment provides a method for preparing an Al-doped transition metal nitride composite coating having both high conductivity and high corrosion resistance, and the specific preparation steps are as follows: S1. TA1 commercial titanium plate was selected as the substrate. The substrate was polished with SiC paper with particle sizes of 240#, 600#, 1000#, 2000# and 3000# in sequence, and then the surface of the substrate was polished into a mirror state with diamond polishing paste with a particle size of 0.5µm; the polished substrate was ultrasonically cleaned with acetone, alcohol and deionized water, and the cleaning time was 15 minutes respectively, and finally the substrate was naturally air-dried.
[0046] S2. The air-dried substrate is fixed on the sample stage and transferred into the deposition chamber. The substrate is heated to 400°C and the vacuum degree of the chamber is less than 2×10 -4 After reaching 400 Pa, high-purity nitrogen was introduced and the nitrogen flow rate was adjusted to keep the nitrogen pressure at around 2 Pa. The deposition target was set to a titanium nitride target with a purity of 99.9%, the laser frequency was set to 8 Hz, the laser energy was set to 3342 mJ, the deposition time was set to 1000 s, and the laser switch was turned on to start depositing the titanium nitride coating.
[0047] S3. After the deposition of the titanium nitride coating is completed, the thickness of the titanium nitride coating is 99.09 nm. Turn off the laser switch and set the deposition target to a titanium aluminum nitride target with a purity of 99.9%, wherein the mass percentage of Al in the titanium aluminum nitride target is 6%, and the mass percentage of titanium nitride is 94%. The substrate temperature, laser frequency and laser energy remain unchanged, the nitrogen pressure is 2 Pa, the deposition time is 1000 s, and the laser is turned on.
[0048] S4, turn off the laser switch, cool naturally to room temperature, take it out from the chamber, the thickness of the titanium aluminum nitride coating is 103.39nm, and finally the Al-doped transition metal nitride composite coating deposited on the surface of the TA1 commercial titanium plate is obtained, and the total thickness of the Al-doped transition metal nitride composite coating is 202.48nm.
[0049] The self-corrosion current density of the coating sample is about 1.04×10 -8 A.cm -2 , at a working voltage of 2.0 V, its corrosion current density is less than 5×10 -7 A.cm -2 , comparable to or even better than the precious metal coatings on the market; the interface contact resistance is about 13.84mΩ·cm 2 While maintaining high corrosion resistance, it also greatly improves the conductivity of the substrate, taking into account both high corrosion resistance and conductivity without the need to load precious metals.
[0050] Compared with Example 1, the nitrogen pressure is changed in this example. The effect of nitrogen pressure on corrosion resistance is mainly caused by the effect on the surface morphology and crystallinity of the coating.
[0051] Comparative Example 1 In this comparative example, a TA1 commercial titanium plate without any treatment was used.
[0052] The self-corrosion current density of the coating sample was about 2.4×10 -4 A.cm -2 At a working voltage of 2.0 V, the corrosion current density is about 1×10 -4 A.cm -2 , poor corrosion resistance.
[0053] Comparative Example 2 In this comparative example, a single-layer titanium nitride coating was prepared by magnetron reactive sputtering after process parameters were optimized, and the preparation method was as follows: S1. TA1 commercial titanium plate was selected as the substrate. The substrate was polished with SiC paper with particle sizes of 240#, 600#, 1000#, 2000# and 3000# in sequence, and then the surface of the substrate was polished into a mirror state with diamond polishing paste with a particle size of 0.5µm; the polished substrate was ultrasonically cleaned with acetone, alcohol and deionized water, and the cleaning time was 15 minutes respectively, and finally the substrate was naturally air-dried.
[0054] S2. The air-dried substrate is fixed on the sample stage and transferred into the deposition chamber. The substrate is heated to 300°C and the vacuum degree of the chamber is less than 5×10 -4 After Pa, high-purity argon gas is introduced and the argon flow rate is adjusted so that the argon flow rate is maintained at about 20 sccm; high-purity nitrogen gas is introduced and the nitrogen flow rate is adjusted so that the nitrogen flow rate is maintained at about 6 sccm.
[0055] S3, use 99.99% pure titanium target as the target target, use the target baffle to block the target, set the sputtering power to 100W, pre-sputter for 15 minutes to remove impurities such as oxides on the surface of the target.
[0056] S4. After the pre-sputtering is completed, the target baffle is removed and the formal sputtering deposition is started. During the deposition process, the sample stage is kept rotating at a constant speed to make the deposition more uniform. The deposition time is 150 minutes, and the thickness of the deposited titanium nitride coating is 372.88 mm.
[0057] S5. Cool naturally to room temperature and remove the sample from the chamber.
[0058] The test shows that the self-corrosion current density of the coating sample is about 5.9×10 -7 A.cm -2 At a working voltage of 2.0 V, the corrosion current density is about 1×10 -5 A.cm -2 , good corrosion resistance, interface contact resistance is about 261.56mΩ·cm 2 , poor conductivity, noble metal loading is 0 mg cm -2 .
[0059] Comparative Example 3 This comparative example provides a method for preparing an Al-doped transition metal nitride composite coating having both high conductivity and high corrosion resistance, and the specific preparation steps are as follows: S1. TA1 commercial titanium plate was selected as the substrate. The substrate was polished with SiC paper with particle sizes of 240#, 600#, 1000#, 2000# and 3000# in sequence, and then the surface of the substrate was polished into a mirror state with diamond polishing paste with a particle size of 0.5µm; the polished substrate was ultrasonically cleaned with acetone, alcohol and deionized water, and the cleaning time was 15 minutes respectively, and finally the substrate was naturally air-dried.
[0060] S2. The air-dried substrate is fixed on the sample stage and transferred into the deposition chamber. The substrate is heated to 400°C and the vacuum degree of the chamber is less than 2×10 -4 After reaching 400 Pa, high-purity nitrogen was introduced and the nitrogen flow rate was adjusted to keep the nitrogen pressure at around 2 Pa. The deposition target was set to a titanium nitride target with a purity of 99.9%, the laser frequency was set to 8 Hz, the laser energy was 3342 mJ, the deposition time was 125 s, and the laser switch was turned on to start depositing the titanium nitride coating.
[0061] S3. Turn off the laser switch and set the deposition target to a titanium aluminum nitride target with a purity of 99.9%, wherein the mass percentage of Al in the titanium aluminum nitride target is 6%, and the mass percentage of titanium nitride is 94%. The substrate temperature, laser frequency and laser energy remain unchanged, the nitrogen pressure is 4 Pa, the deposition time is 125 s, and the laser is turned on.
[0062] S4. Turn off the laser switch, set the deposition target to a titanium nitride target with a purity of 99.9%, keep the substrate temperature, laser frequency and laser energy unchanged, the nitrogen pressure to 4 Pa, the deposition time to 125 s, and turn on the laser.
[0063] S5. Turn off the laser switch and set the deposition target to a titanium aluminum nitride target with a purity of 99.9%, wherein the mass percentage of Al in the titanium aluminum nitride target is 6%, and the mass percentage of titanium nitride is 94%. The substrate temperature, laser frequency and laser energy remain unchanged, the nitrogen pressure is 4 Pa, the deposition time is 125 s, and the laser is turned on.
[0064] S6. Turn off the laser switch, set the deposition target to a titanium nitride target with a purity of 99.9%, keep the substrate temperature, laser frequency and laser energy unchanged, the nitrogen pressure to 4 Pa, the deposition time to 125 s, and turn on the laser.
[0065] S7. Turn off the laser switch and set the deposition target to a titanium aluminum nitride target with a purity of 99.9%, wherein the mass percentage of Al in the titanium aluminum nitride target is 6%, and the mass percentage of titanium nitride is 94%. The substrate temperature, laser frequency and laser energy remain unchanged, the nitrogen pressure is 4 Pa, the deposition time is 125 s, and the laser is turned on.
[0066] S8. Turn off the laser switch, set the deposition target to a titanium nitride target with a purity of 99.9%, keep the substrate temperature, laser frequency and laser energy unchanged, the nitrogen pressure is 4 Pa, the deposition time is 125 s, and turn on the laser.
[0067] S9. Turn off the laser switch and set the deposition target to a titanium aluminum nitride target with a purity of 99.9%, wherein the mass percentage of Al in the titanium aluminum nitride target is 6%, and the mass percentage of titanium nitride is 94%. The substrate temperature, laser frequency and laser energy remain unchanged, the nitrogen pressure is 4 Pa, the deposition time is 125 s, and the laser is turned on.
[0068] S10, turning off the laser switch, cooling naturally to room temperature, taking it out from the chamber, and finally obtaining an Al-doped transition metal nitride composite coating deposited on the surface of a TA1 commercial titanium plate.
[0069] The self-corrosion current density of the coating sample is about 3.98×10 -5 A.cm -2 , the interface contact resistance is about 26.44mΩ·cm 2 , the corrosion resistance and conductivity are poor. This is because during the periodic preparation process of the multi-layer coating, defects in the coating will accumulate, resulting in poor performance.
[0070] See also Figure 4 and Figure 5 The performance test analysis based on Comparative Example 1~Comparative Example 2 and Example 1~Example 2 is as follows: The electrochemical performance test of the corrosion resistance of the samples was carried out using a three-electrode system on an Autolab electrochemical workstation. The tested sample was the working electrode, with an exposure of 1 cm 2 The working area is 200 mm, the counter electrode is a platinum mesh, and the reference electrode is a saturated calomel electrode. The high temperature and strong acid working environment of the bipolar plate of the proton exchange membrane water electrolyzer is simulated. The test electrolyte consists of 0.5 mol / L H2SO4 and 5 ppm fluoride ion solution, and the electrolyte temperature is 80°C. The stable open circuit voltage is measured by immersion in the open circuit for 1 hour. The sample is subjected to a linear voltammetric scan in the potential range of -1V~2V (vs. SCE) at a scanning speed of 1mV / s. The dynamic response of the test sample to the working potential and the effect of the potential on its corrosion resistance are tested. The results are shown in Figure 4 As shown in the figure, the corrosion potential and corrosion current data can be obtained by performing Tafel fitting on the results.
[0071] The self-corrosion current density of Example 1 is 1.0×10 -8 A.cm -2 The self-corrosion current density of Example 2 is 1.15×10 -8 A.cm -2 The self-corrosion current density of comparative example 1 is 2.4×10 -4 A.cm -2 The self-corrosion current density of comparative example 2 is 7.7×10 -7 A.cm -2The composite coating prepared in the example of the present invention has better corrosion resistance than the substrate and the single-layer coating.
[0072] The incorporation of a third element, Al, into the titanium nitride hard coating provides additional benefits, which can improve the corrosion resistance of titanium aluminum nitride due to the formation of Al2O3, excellent temperature, oxidation resistance, and superior mechanical properties. Titanium nitride coatings with relatively low hardness and high corrosion resistance are considered to be adhesive coatings between the metal substrate and the outermost layer. The titanium nitride coating is an enhanced layer in the coating because titanium nitride may provide self-healing properties for the entire coating. Therefore, oxidation of the metal substrate inside the coating can address defects in other coatings. Due to the hardness of titanium aluminum nitride, good conductivity, and superior corrosion resistance of the coating, it can be used as an outer layer.
[0073] Apply 1.5MPa assembly preload force on the sample surface and test its contact resistance. The results are as follows: Figure 5 Under a preload of 1.5 MPa, the contact resistance of Example 1 is 8.55 mΩ·cm 2 The contact resistance of Example 2 is 13.28 mΩ·cm 2 The contact resistance of comparative example 2 is 261.56 mΩ·cm 2 Based on the above comparative analysis, it is proved that the product prepared by the embodiment of the present invention maintains good electrical conductivity while maintaining high corrosion resistance.
[0074] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0075] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. An Al-doped transition metal nitride composite coating, characterized in that: The Al-doped transition metal nitride composite coating is a titanium nitride coating and a titanium aluminum nitride coating deposited sequentially from bottom to top on a substrate; the thickness of the Al-doped transition metal nitride composite coating is 240nm-270nm.
2. The Al-doped transition metal nitride composite coating according to claim 1, characterized in that: The preferred crystal plane orientation of the titanium nitride coating is (200), and the thickness of the titanium nitride coating is 90nm~180nm.
3. The Al-doped transition metal nitride composite coating according to claim 1, characterized in that: The preferred crystal plane orientation of the titanium aluminum nitride coating is (200), and the thickness of the titanium aluminum nitride coating is 90nm~180nm.
4. A method for preparing the Al-doped transition metal nitride composite coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: In a protective gas atmosphere, a titanium nitride target is used as a target material, and a first pulse laser deposition is performed on the surface of the substrate to form a titanium nitride coating; Under a protective gas atmosphere, a titanium aluminum nitride target is used as a target material, and a second pulse laser deposition is performed on the surface of the titanium nitride coating to form a titanium aluminum nitride coating, thereby obtaining an Al-doped transition metal nitride composite coating.
5. The method for preparing an Al-doped transition metal nitride composite coating according to claim 4, characterized in that: In the first pulse laser deposition, the gas pressure of the reaction chamber is 2Pa~4Pa, the deposition temperature is 400°C, and the deposition time is 800s~1000s.
6. The method for preparing an Al-doped transition metal nitride composite coating according to claim 4, characterized in that: In the second pulse laser deposition, the gas pressure of the reaction chamber is 2Pa~4Pa, the deposition temperature is 400°C, and the deposition time is 1000s~1200s.
7. The method for preparing an Al-doped transition metal nitride composite coating according to claim 4, characterized in that: The titanium aluminum nitride target is composed of the following components in mass percentage: aluminum 6%, titanium nitride 94%.
8. The method for preparing an Al-doped transition metal nitride composite coating according to claim 4, characterized in that: The purity of the titanium nitride target is 99.9%, and the purity of the titanium aluminum nitride target is 99.9%.
9. Use of the Al-doped transition metal nitride composite coating according to any one of claims 1 to 3 in a proton exchange membrane fuel cell or a proton exchange membrane water electrolyzer.
10. The use of the Al-doped transition metal nitride composite coating according to claim 9 in a proton exchange membrane fuel cell or a proton exchange membrane water electrolyzer, characterized in that: The Al-doped transition metal nitride composite coating is deposited on the metal bipolar plate.
Citation Information
Patent Citations
High temperature resistance protective coating and preparing method and application thereof
CN106929799A
Metal compound coating, preparation method thereof and modified bipolar plate
CN119592987A
Method of forming a titanium aluminium nitride layer and method of forming a phase-change memory device using the same
KR100852237B1
Ceramic coating for corrosion resistance of nuclear fuel cladding
US20230407453A1
Corrosion resistant coated fuel cell bipolar plate with filled-in fine scale porosities and method of making the same
US6649031B1